Correction of accounting errors through post balance sheet event analysis for Romanian companies - Monica Laura Zlati; Valentin Marian Antohi; Petronela Cardon (Economies, 2019)
Special economic zones (SEZ) can play an integral role in enhancing both regional and national economic growth. To explore the relationship between regional growth and the presence of an SEZ in Songkhla province, Thailand, the CD Vine-Copula AutoRegressive (CD-Vine COPAR) models were constructed using annual datasets of Songkhla's economic performance from 1995 to 2016. The findings indicate that the D Vine-COPAR model produced better fitting predictions for the manufacturing sector, while the C Vine-COPAR models better fit for the agriculture and service sectors. A five-year forecast (2017-2021) was also created. For Vine-COPAR-based Granger causality, the Gross Provincial Production, Foreign Direct Investment and Border Trade are evidently important contributors to regional economic development. Consequently, the government should adopt comprehensive strategies to ensure comparative advantages for operating in the region based on favorable local factors.The study scope is to present the typology of the events analyzed through our research and their impact on the quality of reported financial data. The objectives of the study are to analyze the vulnerability of enterprises according to methodological criteria such as risks and calculations of the risk profile, as well as to establish the necessary measures for correcting the accounting errors based on the conclusions drawn from the analysis. The method used is prospective, financial analysis of the data taken from the financial statements of the companies included in the sample, dynamic for a period of 6 years (2011-2016). Based on the method used, a risk model has been conceptualized to identify the vulnerabilities and risks reported in the financial statements and to define a company risk profile based on which error correction measures can be adopted. Considering the amplitude of the necessary check-ups and the methodology of the imposed accounting treatments, we believe that the topic addressed is a real area of interest for the professional accountants because it organizes the application procedures and limits the impact of errors on the quality of financial reporting in Romania.
Keywords: M41; M21; 330; accounting errors; corrections; accounting treatments; procedures; financial report; IAS-8